'In a blink of an eye your life can change': experiences of players sustaining a rugby-related acute spinal cord injury. Issue 4 (5th July 2018) - Badenhorst, Marelise; Verhagen, Evert; Lambert, Michael Ian; van Mechelen, Willem; Brown, James Craig
Abstract : Background: Though rare, rugby union carries a risk for serious injuries such as acute spinal cord injuries (ASCI), which may result in permanent disability. Various studies have investigated injury mechanisms, prevention programmes and immediate medical management of these injuries. However, relatively scant attention has been placed on the player's experience of such an injury and the importance of context. Aim: The aim of this study was to explore the injury experience and its related context, as perceived by the catastrophically injured player. Methods: A qualitative approach was followed to explore the immediate, postevent injury experience. Semi-structured interviews were conducted with 48 (n=48) players who had sustained a rugby-related ASCI. Results: Four themes were derived from the data. Participants described the context around the injury incident, which may be valuable to help understand the mechanism of injury and potentially minimise risk. Participants also described certain contributing factors to their injury, which included descriptions of foul play and aggression, unaccustomed playing positions, pressure to perform and unpreparedness. The physical experience included signs and symptoms of ASCI that is important to recognise by first aiders, fellow teammates, coaches and referees. Lastly, participants described the e motional experience which has implications for all ASCI first responders. Significance: All rugby stakeholders, including players, first responders, coaches and referees, may gain valuable information from the experiences of players who have sustained these injuries. This information is also relevant for rugby safety initiatives in shaping education and awareness interventions.